1971
DOI: 10.1042/bj1240289
|View full text |Cite
|
Sign up to set email alerts
|

Competitive labelling, a method for determining the reactivity of individual groups in proteins. The amino groups of porcine elastase

Abstract: 1. A method is described for determining the ionization constants and reactivities of individual amino groups in proteins. The principle is that in the presence of a trace amount of radioactive label, the various reactive groups in a protein molecule will compete for the label and the amount incorporated into any one group will be determined by its nucleophilicity, pK and micro-environment. The relative amounts of label incorporated into various groups will be proportional to their second-order rate constants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
93
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 17 publications
2
93
0
Order By: Relevance
“…Furthermore, HEL yields complete sequence data by reproducibly forming abundant proteolytic peptide ions and has a highly stable tertiary structure. Thus, it appears to be well suited as a model protein in chemical modification studies that may affect tertiary structures and reactivities (6,9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, HEL yields complete sequence data by reproducibly forming abundant proteolytic peptide ions and has a highly stable tertiary structure. Thus, it appears to be well suited as a model protein in chemical modification studies that may affect tertiary structures and reactivities (6,9).…”
Section: Discussionmentioning
confidence: 99%
“…Chemical reactivities of amino acid residues have been mainly determined by competitive labeling techniques, which, however, are laborious and generally require radioactive probes (6). For example, acetylation of amino groups has been extensively used for modifying enzymatic properties, immunological reactivity, and proteolytic digestion patterns (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…a conformational change induced by chemical modification. To overcome this problem, the overall degree of labelling is best kept so low that the number of multiply modified protein molecules is negligible (Kaplan et al, 1971 ;Bosshard, 1979). In the case of the biotin-avidin system, probably for the first time used here to map a binding site by the differential protection technique, the degree of biotinylation had to be greater than one molecule biotidprotein molecule because the amount of FNR available in the experiment was limited.…”
Section: Experimental Approachmentioning
confidence: 99%
“…Kaplan and his associates (Kaplan et al 1971) have shown that the method of competitive labelling with electrophilic reagents in the presence of a standard nucleophile is a valid and valuable method to determine pK values of nucleophilic residues in native proteins. The results obtained for elastase (Kaplan et al 1971), chymotrypsin (Kaplan 1972) and calf thymus histones (Malchy and Kaplan 1974) agree well with results obtained from other evidence.…”
Section: Introductionmentioning
confidence: 99%